Engineering Spiny PtFePd@PtFe/Pt Core@Multishell Nanowires with Enhanced Performance for Alcohol Electrooxidation - Zhang, Yangping; Gao, Fei; Wang, Caiqin; Shiraishi, Yukihide; Du, Yukou (ACS applied materials & interfaces, 2019)
Engineering robust electrocatalysts is always a key point in direct alcohol fuel cells. Catalysts with a one-dimension (1D) structure are well studied and considered as promising candidates among various catalysts in the past decades; however, the precise regulation on the surface structure of 1D nanomaterials is still a worthy subject. By creatively introducing a trimetallic nanoalloy, core@multishell structure, and 1D nanowire (NW) morphology, we have constructed a kind of novel spiny PtFePd@PtFe/Pt core@multishell 1D NW catalysts with PtFePd as the core and PtFe/Pt as the multishell on the basis of improving catalytic property. The composition-optimized Pt5FePd2 1D NWs display remarkable catalytic properties for ethanol oxidation reaction and methanol oxidation reaction, in which mass activities are 4.965 and 4.038 A mg–1, 4.6 and 5.0 and 4.0 and 9.2-fold higher than Pt/C and Pd/C catalysts. Furthermore, the obtained Pt5FePd2 NWs can also retain favorable stability after durability tests. The unique core@multishell structure, spiny 1D NWs with many steps and kinks, and interior electronic and synergistic effect all contribute to the advanced catalytic performance. The present work has rationally designed the novel 1D PtFePd@PtFe/Pt core@multishell NW catalysts and offered a meaningful guideline for the designing of high-performance electrocatalysts.